2014
DOI: 10.1002/gps.4154
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aging on insight into illness in schizophrenia: a review

Abstract: Objectives Impaired insight into illness is a prevalent feature of schizophrenia, which negatively influences treatment adherence and clinical outcomes. Little is known about the effects of aging on insight impairment. We aimed to review the available research literature on the effects of aging on insight into illness in schizophrenia, in relation to positive, negative, and cognitive symptoms. Ultimately, we propose a trajectory of insight in schizophrenia across the lifespan. Method A systematic Medline® li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 182 publications
(260 reference statements)
3
47
1
1
Order By: Relevance
“…Although this study was designed to include participants with moderate to severe IMP-INS, for the most part, participants were clinically stable with minimal positive symptoms and good awareness of the need for treatment (Table 1). That being said, minimal symptom severity helps ensure the specificity of CVS for IMP-INS as symptom severity and IMP-INS are strongly correlated (Gerretsen et al, 2014b). Relatedly, it is difficult to determine the clinical significance of impaired illness awareness in a sample that accepts the need for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study was designed to include participants with moderate to severe IMP-INS, for the most part, participants were clinically stable with minimal positive symptoms and good awareness of the need for treatment (Table 1). That being said, minimal symptom severity helps ensure the specificity of CVS for IMP-INS as symptom severity and IMP-INS are strongly correlated (Gerretsen et al, 2014b). Relatedly, it is difficult to determine the clinical significance of impaired illness awareness in a sample that accepts the need for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…“the voices are imaginary due to my mind playing tricks on me”), awareness of need for treatment (“I need an antipsychotic in order to stay mentally healthy”), and awareness of negative consequences attributable to the illness (“I have difficulty working because of schizophrenia” or “I was in jail because I was psychotic”). For in depth reviews on the topic, the reader is directed to Gerretsen et al (2014) (Gerretsen et al, 2014b) and Chakraborty and Basu (2010) (Chakraborty and Basu, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Cernis et al 127 identified a subgroup with a premorbid IQ estimated as 120 or greater and found that they had better clinical insight than peers with typical levels of intellectual function. To explain these inconsistencies, it has been proposed that the relationship between insight and neurocognition may depend upon the phase of life 128,129 and that good neurocognitive function may be a necessary but not a sufficient condition for clinical insight 130 .…”
Section: Neurocognition As a Root Of Poor Insightmentioning
confidence: 99%
“…Previous studies investigating insight longitudinally or comparing illness insight in firstepisode and multiepisode patients have yielded mixed results. A recent systematic review showed that the course of illness insight follows a U-shaped curve, where insight is severely impaired in first-episode patients, modestly improves over midlife and declines in later life (Gerretsen et al, 2014). However, conflicting results showed better insight in multiepisode patients in comparison with FES patients (Thompson et al, 2001) or no significant differences between both groups (Comparelli et al, 2013).…”
Section: Discussionmentioning
confidence: 99%